Specific high affinity interaction of Helicobacter pylori CagL with integrin αVβ6 promotes type IV secretion of CagA into human cells. (27th June 2019) - Buß, Maren; Tegtmeyer, Nicole; Schnieder, Jennifer; Dong, Xianchi; Li, Jing; Springer, Timothy A.; Backert, Steffen; Niemann, Hartmut H.
Abstract : The bacterial pathogen Helicobacter pylori can cause gastric cancer in humans. Helicobacter pylori uses a type IV secretion system (T4SS) to inject the oncogenic protein CagA into stomach epithelial cells. In this study, Hartmut Niemann and colleagues show that the T4SS pilus protein CagL binds the host cell receptor integrin αV β6 with high affinity. This interaction promotes CagA injection into human cells, suggesting that αV β6 plays an important role during H. pylori infection. Abstract : CagL is an essential pilus surface component of the virulence‐associated type IV secretion system (T4SS) employed by Helicobacter pylori to translocate the oncogenic effector protein CagA into human gastric epithelial cells. CagL contains an RGD motif and integrin α5 β1 is widely accepted as its host cell receptor. Here, we show that CagL binds integrin αV β6 with substantially higher affinity and that this interaction is functionally important. Cell surface expression of αV β6 on various cell lines correlated perfectly with cell adhesion to immobilized CagL and with binding of soluble CagL to cells. We found no such correlation for α5 β1 . The purified αV β6 ectodomain bound CagL with high affinity. This interaction was highly specific, as the affinity of CagL for other RGD‐binding integrins was two to three orders of magnitude weaker. Mutation of either conserved leucine in the CagL RGDLXXL motif, a motif that generally confers specificity for integrin αV β6 and αV β8, lowered the affinity of CagL for αV β6 . Stable expression of αV β6 in αV β6 ‐negative but α5 β1 ‐expressing human cells promoted two hallmarks of the functional H. pylori T4SS, namely translocation of CagA into host cells and induction of interleukin‐8 secretion by host cells. These findings suggest that integrin αV β6, although not essential for T4SS function, represents an important host cell receptor for CagL.